LEGAL MEASURES IN HANDLING CRIMINAL ACTS IN CORPORATE PERSPECTIVE LAW NO. 20 OF 2021 CONCERNING CRIMINAL ACTS OF CORRUPTION - M. Fajri Hidayatullah; Novita Aulia Lubis; Mhd. Ihwanuddin Hasibuan; Rico Nur Ilham (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Corruption is a culture that is very difficult to get rid of, especially related to corporations and government agencies which are very vulnerable to occur and this is an action that is very detrimental to the state and has a lasting effect on future regeneration, especially in Indonesia which is no stranger to experiencing corruption problems. This can be considered a problem. Corruption is an ordinary crime problem, this is a wrong statement for ordinary people who think this is normal. But we need to underline that corruption is an act that has a very large negative impact compared to other criminal problems, whatever the form of the problem that leads to criminal acts of corruption, it is certain that it is very fatal and cannot be tolerated. According to the large legal dictionary which states that corruption is included in the realm of extraordinary crime, it is an extraordinary crime that is special in handling and by law it overrides general legislation. If we relate it to the criminal law system that we have, in dealing with corruption problems that occur in the corporate area, we also experience the same thing, namely difficulties in application and implementation, why is that? requires the ability to think intelligently and a strict system and is required to have a pattern of good thinking.